Wissen Macht Tracht im Ötztal - Neuner-Schatz, Nadja (Bricolage monografien, 2018)
"This ethnographic study first analyzes the historical genesis of a specific, ethnographic body of knowledge, the knowledge of ""Tracht"" in the Ötztal, and then to ask for the current update of this knowledge in doing ""costume"" of self-producing actors. The results show that the act of ""traditional"" acting actors is situated in a field structured by power and knowledge. For this field of ""traditional"" practice and ""traditional"" knowledge it is possible to observe how the current actors cite and repeat folklore knowledge strategies. The analysis and historicization of these knowledge strategies show the long-term effectiveness of folkloristic knowledge. At the same time, the example of the ""costume"" of self-production can be used to ask about moments of cultural negotiation and change. Nadja Neuner-Schatz, MA studied European Ethnology in Innsbruck and researches on ethnographic production/folkloristic knowledge in the modern age, phenomena of subalternisation and the Human-Animal-Studies."